(untitled) (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2025)
This study aims to identify the factors and processes of self-acceptance in girls who experience fatherlessness. Fatherlessness can occur due to the absence of a father figure physically or emotionally, and this significantly affects the development of self-acceptance in individuals. This research employed a qualitative approach with a descriptive phenomenological method, using Albert Ellis’ theory of Unconditional Self-Acceptance as the theoretical foundation. The participants were two female university students who experienced fatherlessness in different ways, one due to being raised by extended family and the other due to an unhealthy emotional relationship with her father. Data were collected through semi-structured interviews, observation, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings show that the process of self-acceptance is dynamic and full of challenges, marked by negative emotions such as anger, disappointment, and insecurity. Factors influencing self-acceptance include social support, self-reflection, and the presence of substitute father figures. A significant finding is that sincerity (ikhlas) plays a crucial role in helping individuals achieve unconditional self-acceptance. The study suggests that girls experiencing fatherlessness should continue to develop self-understanding and self-compassion, as well as seek positive social support. Future researchers are encouraged to expand the participant pool and utilize more structured interview guides to enrich the depth and variety of data.